A generalized control law for uniform, global and exponential magnetic detumbling of rigid spacecraft. Issue 2 (2020) - Petit, Nicolas; Sarras, Ioannis
Abstract: The problem of magnetic detumbling, also known as magnetic momentum unloading, is considered. The objective is to stabilize a rigid spacecraft angular velocity to zero only through magnetic actuation, i.e. magneto-torquers. We propose a generalized control law that is uniformly, globally exponentially stabilizing (UGES) and show that the celebrated b-dot law is one particular case of this law. Furthermore, we provide an explicit (time-varying) strict Lyapunov function to establish the stability claim.